2003
DOI: 10.1111/j.1365-2621.2003.tb05798.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Chemically Defined Medium for Growth of Bifidobacterium animalis

Abstract: The growth of Bifidobacterium animalis was tested, under batch and continuous culture conditions, for dependence upon specific nitrogen compounds. The addition of nitrogen bases (adenine, xantine, and guanine) to the medium containing acid-hydrolyzed casein significantly affected the growth of B. animalis, whereas no significant growth was reported when those bases were added to the medium containing only free amino acids; B. animalis was characterized by a max of 0.16/h when growth took place in PROLAB medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…In vivo, the activity of DNA-cytosine methyltransferase (EC 2.1.1.37) may contribute to the formation of S-adenosyl-L-homocysteine. Besides cysteine and methionine, in silico predictions further suggested that BB-12 and BB-46 can use peptides as an organic sulfur source, which agrees with former studies demonstrating the ability of bifidobacteria to grow in a medium containing hydrolyzed casein instead of free amino acids 38 , 39 .
Fig.
…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In vivo, the activity of DNA-cytosine methyltransferase (EC 2.1.1.37) may contribute to the formation of S-adenosyl-L-homocysteine. Besides cysteine and methionine, in silico predictions further suggested that BB-12 and BB-46 can use peptides as an organic sulfur source, which agrees with former studies demonstrating the ability of bifidobacteria to grow in a medium containing hydrolyzed casein instead of free amino acids 38 , 39 .
Fig.
…”
Section: Resultssupporting
confidence: 87%
“…No CDM reported in literature for bifidobacteria contained the combination of pantethine, menaquinone-4, and nicotinic acid 38 – 41 , which explains their inability to sustain reproducible growth of BB-12 and BB-46 in this study for multiple subcultures. Even though early publications described pantethine as an essential growth factor for Bifidobacterium strains 36 , 44 , 47 , 48 , several newer studies on medium development for bifidobacteria have ignored this finding 39 – 41 . For example, a previously developed CDM for a B. animalis strain lacked pantethine and nicotinic acid 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Bifidobacterium breve UCC2003 (previously designated NCIM B8807), originally isolated from an infant nursing stool (Ventura et al, 2004b), was routinely cultured in reinforced clostridial medium (RCM) at 37 uC in an anaerobic chamber (Don Whitley Scientific). Where mentioned, a defined medium (DM) based on that described by Kongo et al (2003) was used to culture B. breve, with glycine betaine (Sigma) being added as a filter-sterilized solution. Escherichia coli MKH13 was grown in Luria-Bertani (LB) medium at 37 uC with agitation.…”
Section: Methodsmentioning
confidence: 99%
“…animalis in small ruminant milk media (Gomes and Malcata 1998a,b), in cow milk (Gomes et al. 1995, 1998) and in artificial medium (Kongo et al. 2003) have been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…acidophilus and Bif. animalis in small ruminant milk media (Gomes and Malcata 1998a,b), in cow milk (Gomes et al 1995(Gomes et al , 1998 and in artificial medium (Kongo et al 2003) have been undertaken. Other studies within our group (not published) have also shown a commensalistic growth relation in mixed cultures of Lact.…”
Section: Introductionmentioning
confidence: 99%